Anti-EGFR liquid crystalline nanodispersions for docetaxel delivery: Formulation, characterization and cytotoxicity in cancer cells - Trevizan, Lucas Noboru Fatori [UNESP]; Eloy, Josimar O.; Luiz, Marcela Tavares; Petrilli, Raquel; Junior, Sergio Luiz Ramos; Borges, Julio César; Marchetti, Juliana Maldonado; Chorilli, Marlus [UNESP] (Elsevier, 2021)
Prostate cancer is one of the most frequent neoplasms, associated with high mortality. Some factors may intensify its aggressiveness, for example, the overexpression of the epidermal growth factor receptor (EGFR) in some subtypes of prostate tumors. In this context, the inhibition of EGFR helps to fight neoplasia, with the use of the chimeric anti-EGFR monoclonal antibody, cetuximab (CTX). For cancer treatment in the metastatic stage, chemotherapy using docetaxel (DTX) is widely employed, however the drug is very liposoluble, hampering its bioavailability. In this sense, liquid crystalline systems have great potential for the delivery of DTX. Particularly, liquid crystalline nanodispersions can be used in parenteral routes, with many advantages, including the possibility of prolonged drug release, improved pharmacokinetics, allowing passive tumor accumulation by the EPR effect. Thus, the objective of this work was to develop a liquid crystalline nanodispersion (LCN) based on ethoxylated cetyl alcohol 20 and propoxylated 5 as surfactant (Procetyl®), oleic acid, DSPE-PEG-MAL (anchor for CTX binding) and soy phosphatidylcholine as oily phase and 1.5 % poloxamer dispersion in PBS buffer as an aqueous phase. The formulation was loaded with DTX and covalently functionalized with CTX to evaluate its cytotoxic potential against prostate cancer cells. The results suggested that the obtained system has a predominantly hexagonal crystalline phase, was able to be nanodispersed with low polydispersity, and presented negative zeta potential. CTX did not have its structure compromised after thiolation and was successfully covalently linked to LCN. In a prostate cancer cells, PC3, LCNs functionalized with CTX underwent greater cell uptake, resulting in greater cytotoxicity, compared to free DTX and non-functionalized DTX-loaded LCNs. Therefore, the present study reports for the first time an EGFR-targeted liquid crystal nanodispersion for selective to deliver DTX to prostate cells
Keywords: Cetuximab; Docetaxel; Hexosome; Liquid crystal; Nanodispersion